1975
DOI: 10.1002/bbpc.19750790708
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung der selbst‐sensibilisierten Photooxidation des Rubrens in verschiedenen Lösungsmitteln

Abstract: Die Gesamtquantenausbeute der selbst‐sensibilisierten Photooxidation des Rubrens wurde in Benzol, Toluol, Chloroform, 1,2,4‐Trichlor‐benzol, Tetrachlorkohlenst off und Schwefelkohlenstoff in Abhängigkeit von der Sauerstoffkonzentration und der Rubrenkonzentration bei 25 ± 2°C gemessen. Weiterhin wurden die relativen Fluoreszenzquantenausbeuten, die Fluoreszenzabklingdauern und die Konstanten für die Sauerstofflöschung der Fluoreszenz ermittelt. Die Analyse der kinetischen Daten steht mit der Annahme im Einklan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Figure shows the excellent linear plot obtained with the CHCl 3 data, with the intercept for = 2 at 1 − ( F / F 0 ) = 1. Thus, Brauer and Wagner first demonstrated that both the T 1 state and O 2 ( 1 Δ g ) may be formed during the fluorescence quenching by O 2 and that the maximum value of Q Δ is 2 . This important result was confirmed by both authors in the subsequent investigation of the self-sensitized photo-oxygenation of heterocoerdianthrone .…”
Section: Products Of S1-state Quenchingmentioning
confidence: 76%
See 4 more Smart Citations
“…Figure shows the excellent linear plot obtained with the CHCl 3 data, with the intercept for = 2 at 1 − ( F / F 0 ) = 1. Thus, Brauer and Wagner first demonstrated that both the T 1 state and O 2 ( 1 Δ g ) may be formed during the fluorescence quenching by O 2 and that the maximum value of Q Δ is 2 . This important result was confirmed by both authors in the subsequent investigation of the self-sensitized photo-oxygenation of heterocoerdianthrone .…”
Section: Products Of S1-state Quenchingmentioning
confidence: 76%
“…Division by the corresponding reaction efficiencies f R yielded values of + S Δ = 1.6 (toluene), 1.7 (benzene), 2.1 (CHCl 3 ), 1.7 (C 6 H 3 Cl 3 ), 1.9 (CCl 4 ), and 2.1 (CS 2 ). Since , , and S Δ cannot be larger than 1, this result clearly indicates that, for rubrene, both processes 52 and 58 contribute to O 2 ( 1 Δ g ) formation, with efficiencies near or equal to unity …”
Section: Products Of S1-state Quenchingmentioning
confidence: 80%
See 3 more Smart Citations